Efektivitas Instrumen Asesmen Afektif dalam Meningkatkan Kualitas Pembelajaran Bahasa Indonesia - Ayu Atikah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research describes the development and implementation of affective assessment instruments in the context of Indonesian language learning in five junior high schools in Padang. The research used a four-cycle Classroom Action Research (PTK) design with the participation of five teachers and twenty-five eighth grade students. Research instruments include questionnaires, structured interviews, class observations, and student reflective journals to collect data about students' attitudes, interests, motivation and values ​​towards Indonesian language lessons. Data analysis uses qualitative and quantitative approaches, including descriptive, inferential and thematic statistical analysis. The research results show that affective assessment instruments are effective in increasing student understanding and learning motivation, as well as supporting the development of adaptive and responsive teaching strategies. The practical implication is the importance of integrating affective assessment in education to improve the quality and readiness of students to face the challenges of future learning.